2019 34th Annual ACM/IEEE Symposium on Logic in Computer Science (LICS) 2019
DOI: 10.1109/lics.2019.8785848
|View full text |Cite
|
Sign up to set email alerts
|

Bisimulation Equivalence of First-Order Grammars is ACKERMANN-Complete

Abstract: Checking whether two pushdown automata with restricted silent actions are weakly bisimilar was shown decidable by Sénizergues (1998Sénizergues ( , 2005. We provide the first known complexity upper bound for this famous problem, in the equivalent setting of first-order grammars. This ACKERMANN upper bound is optimal, and we also show that strong bisimilarity is primitive-recursive when the number of states of the automata is fixed.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…The restriction on silent actions is a decidability border since Jančar and Srba showed that weak bisimilarity between general PDA is undecidable [11]. Yin et al proved that branching bisimilarity between PDA is also undecidable [12].…”
Section: Introductionmentioning
confidence: 99%
“…The restriction on silent actions is a decidability border since Jančar and Srba showed that weak bisimilarity between general PDA is undecidable [11]. Yin et al proved that branching bisimilarity between PDA is also undecidable [12].…”
Section: Introductionmentioning
confidence: 99%
“…A central ingredient to this semi-decision procedure is an oracle call to test the equivalence of pushdown systems, the latter itself being an intricate problem whose decidability has been proven by Sénizergues [27]. Only recently an Ackermannian upper bound for bisimilarity of pushdown system has been proven by Jančar and Schmitz [17]; ACKER-MANN-hardness is only known to hold in the presence of deterministic ε-popping rules [13], whereas without ε-rules the problem is nonelementary [2]. Coming back to bisimulation finiteness of pushdown systems, the oracle calls to a bisimulation equivalence check for pushdown systems is the inherent bottleneck of Jančar's approach.…”
Section: Introductionmentioning
confidence: 99%